Retrospective evaluation of computed tomographic‐guided Tru‐Cut biopsies in 16 dogs and 14 cats with nasal cavity mass lesions - Jessica Milne; Sophie Ekkebus; Daniel Thompson; Robert Brash (Journal of Veterinary Internal Medicine)
Abstract Background Approximately 80% of nasal masses in dogs and 91% of nasal masses in cats are reported to be malignant, but the currently reported diagnostic rate of neoplasia is 54% using blind or rhinoscopic biopsy techniques. Hypothesis/Objectives Describe the technique of computed tomography (CT)‐guided Tru‐Cut (Tru‐Cut biopsy needle, Merit Medical Systems, Utah, USA) nasal biopsies in cats and dogs to determine the diagnostic rate of neoplasia on the first round of sampling and to evaluate the safety of the technique. Animals Thirty client‐owned animals, 16 dogs and 14 cats, that had CT‐guided nasal biopsies performed to investigate nasal masses. Methods Retrospective, single‐center, medical record review of 16 dogs and 14 cats that had CT‐guided nasal biopsies performed between 2022 and 2024. Results Diagnostic biopsy samples were acquired using CT‐guided Tru‐Cut sampling in 28/30 cases (93%). The diagnosis was considered clinically appropriate in 26/30 cases (87%): neoplasia in 24/30 cases (80%) and rhinitis in 2/30 cases (7%). Neoplasia was the final diagnosis in 14/16 dogs (88%) and 10/14 cats (71%). Conclusions and Clinical Importance Computed tomographic‐guided Tru‐Cut biopsies can result in a high first‐round diagnosis of neoplasia in nasal masses in cats and dogs, without clinically relevant complications. This technique is a useful alternative method of sampling nasal masses that may be difficult to access via rhinoscopy.